Pengaruh lama pemeraman dengan tingkat jumlah garam yang berbeda terhadap uji organoleptik telur asin - Herlinae Herlinae; Yemima Yemima; Rani Rani (Fakultas Peternakan Universitas Kristen Palangka Raya, 2018)
The aim of this research is to know the effect of egg curing duration on salt egg organoleptic test, to know the influence of salt level to salt egg organoleptic test, and interaction between curing duration and salt amount to organoleptic test of salted egg. This study was conducted using a complete randomized design using two factors, namely the duration of curing time (A) and the level of salt amount (B). Parameters observed included taste, color, smell / aroma, and texture of salted eggs using panelist assessments. The results showed that the organoleptic test of salted egg samples on flavor, color, aroma, and texture had no effect, while the interaction had significant effect.